Figurative meaning construction in thought and language - Baicchi, Annalisa (Figurative thought and language, 2020)
"This volume brings together twelve usage-based studies conducted by leading researchers in language and cognition that explore core issues of figurativeness from the Cognitive Linguistics perspective. The individual chapters reveal the central function of figurativeness in thought and its impact on language. Cognition relies on knowledge-structuring tools in the construction of meaning both mentally and linguistically. Collectively, the chapters delve into an array of topics that are crucial to future research in figurative meaning construction, especially on questions of identification and structure of figures, the figurative motivation of constructions, the impact of figurativeness on pragmatic and multimodal communication, and the correlation between figures and cognitive models"--